General chemistry / Donald A McQuarrie; Peter A Rock; Ethan B Gallogly - McQuarrie, Donald A
Atoms First seems to be the flavor of the year in chemistry textbooks, but many of them seem to be little more than rearrangement of the chapters. It takes a master like McQuarrie to go back to the drawing board and create a logical development from smallest to largest that makes sense to students."--Hal Harris, University of Missouri-St. Louis.